Automated Phylogenetic Analysis Using Best Reciprocal BLAST - Butterfield, Erin R; Abbott, James C; Field, Mark C (Methods in molecular biology (Clifton, N.J.), 2021)
Reconstruction of the evolutionary history of specific protein-coding genes is an essential component of the biological sciences toolkit and relies on identification of orthologs (a gene in different organisms related by vertical descent from a common ancestor and usually presumed to have the same or similar function) and paralogs (a gene related to another in the same organism by descent from a single ancestral gene which may, or may not, retain the same/similar function) across a range of taxa. While obviously essential for the reconstruction of evolutionary histories, ortholog identification is of importance for protein expression, modeling for drug discovery programs, identification of critical residues and other studies. Here we describe an automated system for searching for orthologs and paralogs in eukaryotic organisms. Unlike manual methods the system is fast, requiring minimal user input while still being highly configurable.
Keywords: Automation; Evolution, Molecular; Drug discovery; Evolution; Sequence searching; Phylogenetics; Phylogeny; Ortholog; Homology; molekulární evoluce; fylogeneze